2016
DOI: 10.1186/s13256-016-1010-8
|View full text |Cite
|
Sign up to set email alerts
|

Occipital lobe seizures and subcortical T2 and T2* hypointensity associated with nonketotic hyperglycemia: a case report

Abstract: BackgroundNonketotic hyperglycemia often causes seizures. Recently, seizures associated with nonketotic hyperglycemia have been found to be associated with subcortical T2 hypointensity on magnetic resonance imaging, especially in the occipital lobes. However, the mechanism remains unclear, although iron accumulation is suggested. We present a case of occipital lobe seizures associated with nonketotic hyperglycemia supporting the hypothesis that the mechanism of subcortical T2 hypointensity is iron accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…In one report, disrupted blood brain barrier (BBB) as evident on delayed gadolinium enhancement in FLAIR images, was suggested to play a role in seizure formation in this setting [7]. Sasaki et al, suggest that long-standing hyperglycemia, rather than HHS per say, is the trigger for seizure as their patient did not meet diagnostic criteria of HHS [8].…”
Section: Discussionmentioning
confidence: 99%
“…In one report, disrupted blood brain barrier (BBB) as evident on delayed gadolinium enhancement in FLAIR images, was suggested to play a role in seizure formation in this setting [7]. Sasaki et al, suggest that long-standing hyperglycemia, rather than HHS per say, is the trigger for seizure as their patient did not meet diagnostic criteria of HHS [8].…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Previous studies and reported cases of patients with slightly elevated serum osmolarity suggest the role of long-standing hyperglycaemia with abnormal HbA1c levels in inducing seizures, rather than an acute hyperglycaemic hyperosmolar state. 4,6,7 NKH-induced seizures are mostly of a focal motor type with or without secondary generalisation. Cases of epilepsia partialis continua and visual occipital lobe seizures have been described.…”
Section: Discussionmentioning
confidence: 99%
“…The transient iron accumulation may explain the corresponding hypointensity sometimes seen on T2*-weighted or SWI images. 7,17 Early post-ictal brain MRI shows brain abnormalities that involve mostly the cortical grey matter. Cortical hyperintensity on T2/FLAIR images with restricted diffusion, often associated with gyral or leptomeningeal gadolinium enhancement, are widely reported in association with seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 7 ] The leptomeningeal enhancement is an unusual manifestation in hyperglycemic state but has been reported in cases with hyperglycemia-related seizures. [ 4 8 ] The associated differential diagnosis of leptomeningeal enhancement with subcortical T2 hypointensity includes focal patchy meningitis, encephalitis, hemorrhagic infarcts, malignancy, and paraneoplastic process. [ 6 ] Almost these etiologies can be excluded in our case on the basis of patient's history and clinical manifestations with a shortly reversible clinical course and MRI abnormalities.…”
Section: Discussionmentioning
confidence: 99%